Activation of human bitter taste receptors by polymethoxylated flavonoids*. Issue 10 (2nd October 2016) - Kuroda, Yuki; Ikeda, Riko; Yamazaki, Toyomi; Ito, Keisuke; Uda, Kazunari; Wakabayashi, Keiji; Watanabe, Tatsuo
Abstract : Tangeretin and nobiletin are polymethoxylated flavonoids in citrus peel. Both tangeretin and nobiletin are bitter; however, their bitterness has not been evaluated using human bitter taste receptors (hTAS2Rs). We screened 25 kinds of hTAS2Rs and found that hTAS2R14 and hTAS2R46 received both compounds.